Piger på nettet. Repræsentationer af unge kvinders seksualitet i den digitale tidsalder - Flanagan, Victoria (Passage - Tidsskrift for litteratur og kritik, 2016)
“Girls Online. Representations of Adolescent Female Sexuality in the Digital Age” Media representations of social media and cyberspace often emphasise their negative social impact for adolescent girls. There is the potential, however, for virtual reality to function as a pro-feminist space that enables young women to form supportive, networked communities. A number of YA fictions published post-2005 adopt this type of representational paradigm and explicitly seek to construct a positive relationship between feminine subjectivity and digital technology. This article will focus particularly on how three YA narratives – L8r, g8r (2007) by Lauren Myracle, Fangirl (2013) by Rainbow Rowell and the short story “Tumbling” (2014) by Susie Day – comment on the manner in which social media has affected the expression of female sexual desire in the digital age. These YA fictions provide young readers with progressive representations of adolescent female sexuality that acknowledge and validate female desire and also showcase the positive role that online social networks can play in nurturing unconventional and empowered expressions of female sexuality.